Imagem, Informação e Memória abordagens acerca da preservação do audiovisual, do cinema e da fotografia - Manini, Miriam Paula (Editora Oficina Universitária, 2022)
The research community's interest in information studies that address visual records in their most diverse information resources is present. In this book, the discussion on the dimension of images in the context of photographs, cinematographic works and other audiovisual documents was chosen through the bias of memory and also with regard to the preservation of these documents. Humanity's historical and cultural trajectory, linked to visual records, boosted the development of techniques and technologies that implied, in one way or another, theories and practices related to the organization of these documents, through their analysis and interpretation. The latter allowed their technical treatment, packaging, access and use in the contexts of memory-information units, whether physical or digital spaces, in addition, of course, to the memory-information environments that are configured on the internet and social networks. The chapters in this book show the choice of approaches to the paths taken by its authors, whose authorial distinction was directed or pervaded in the approaches regarding the complexity of photographic and audiovisual collections in custodial institutions and their organization, memory as a report and cognitive perspective and audiovisual preservation . In order to allocate the subjects addressed, the work is divided into three blocks: Audiovisual, Information and Memory (AIM), Cinema, Information and Memory (CIM) and Photography, Information and Memory (FIM). Such a division is purely a "manic" exercise of putting into pigeonholes everything that is considered classifiable, cataloguable. As a whole, we are all members of the same party of the image.